2021
DOI: 10.3390/cells10071658
|View full text |Cite
|
Sign up to set email alerts
|

The Role of cAMP in Beta Cell Stimulus–Secretion and Intercellular Coupling

Abstract: Pancreatic beta cells secrete insulin in response to stimulation with glucose and other nutrients, and impaired insulin secretion plays a central role in development of diabetes mellitus. Pharmacological management of diabetes includes various antidiabetic drugs, including incretins. The incretin hormones, glucagon-like peptide-1 and gastric inhibitory polypeptide, potentiate glucose-stimulated insulin secretion by binding to G protein-coupled receptors, resulting in stimulation of adenylate cyclase and produc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 232 publications
(376 reference statements)
0
20
0
Order By: Relevance
“…This seems to be supported by the observation that oscillations in [Ca 2+ ] IC and cAMP are typically in phase or occur with a slight shift. Pharmacological activation of GLP-1 receptors and/or direct activation of adenylate cyclase by forskolin are unable to stimulate beta cells in low glucose but can significantly enhance glucose-stimulated Ca 2+ oscillations ( 180 182 ). Indeed, by constructing functional connectivity networks we have recently shown that increasing cAMP levels using forskolin increases beta cell activity as well as enhances synchronicity and coordination of intercellular signaling, evident as denser and more integral networks ( 180 , 183 ).…”
Section: Functional Implications Of Beta Cell Network Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This seems to be supported by the observation that oscillations in [Ca 2+ ] IC and cAMP are typically in phase or occur with a slight shift. Pharmacological activation of GLP-1 receptors and/or direct activation of adenylate cyclase by forskolin are unable to stimulate beta cells in low glucose but can significantly enhance glucose-stimulated Ca 2+ oscillations ( 180 182 ). Indeed, by constructing functional connectivity networks we have recently shown that increasing cAMP levels using forskolin increases beta cell activity as well as enhances synchronicity and coordination of intercellular signaling, evident as denser and more integral networks ( 180 , 183 ).…”
Section: Functional Implications Of Beta Cell Network Analysismentioning
confidence: 99%
“…Pharmacological activation of GLP-1 receptors and/or direct activation of adenylate cyclase by forskolin are unable to stimulate beta cells in low glucose but can significantly enhance glucose-stimulated Ca 2+ oscillations ( 180 182 ). Indeed, by constructing functional connectivity networks we have recently shown that increasing cAMP levels using forskolin increases beta cell activity as well as enhances synchronicity and coordination of intercellular signaling, evident as denser and more integral networks ( 180 , 183 ). While both slow and fast Ca 2+ oscillations rely on periodic entry of Ca 2+ from extracellular space into the beta cells through voltage-activated Ca 2+ channels, the fast Ca 2+ oscillations may also depend on mobilization of intracellular Ca 2+ stores from the endoplasmic reticulum.…”
Section: Functional Implications Of Beta Cell Network Analysismentioning
confidence: 99%
“…Glucose influx into pancreatic beta-cells followed by an increase in glucose metabolism elevates cytosolic adenosine triphosphate (ATP) concentration, closing ATP-dependent K+ (KATP) channels and decreasing K+ efflux. Consequent cell membrane depolarization opens voltage-dependent Ca2+ (VDCC) channels and Ca2+ ions influx, which triggers insulin secretion [ 134 , 135 , 136 ]. The predominant UCP in beta-cells is UCP2, which regulates cellular oxidative stress, ROS production, and energy metabolism, and protects mice from aging [ 137 , 138 ].…”
Section: Ucp2 and Insulin Secretion In Pancreatic Beta-cellsmentioning
confidence: 99%
“…The binding of GLP-1 to GLP-1 receptor activates adenylate cyclase, leading to increased cAMP levels. PKA and EPAC are then activated, which induces an increase in intracellular Ca 2+ from the ER and extracellular sources via voltage-dependent Ca 2+ channels [128,129]. Additionally, the activation of PKA by GLP-1 leads to the activation of pancreatic duodenal homeobox-1 protein (PDX-1), which binds to the promoter of the gene encoding insulin and induces the synthesis of insulin [128,130] (Figure 3).…”
Section: Glucose Metabolismmentioning
confidence: 99%